DETERMINANTS OF ATTITUDE AND ADOPTION INTENTION OF ISLAMIC FINANCING IN TASIKMALAYA: A BEHAVIORAL INTENTION FRAMEWORK APPROACH - Andani, Listia; Mutmainah, Lu'liyatul; Hidayat, Deny; Berakon, Izra (Finansha: Journal of Sharia Financial Management, 2025)
This study explores the determinants of Muslim entrepreneurs’ intention to adopt Islamic finance in Tasikmalaya using the extended Theory of Planned Behavior (TPB). It examines the roles of religiosity, awareness, financial literacy, knowledge, attitude, subjective norms, and perceived behavioral control. A quantitative approach was applied, with purposive sampling of 250 respondents who had not previously adopted Islamic financing. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that attitude, subjective norms, and perceived behavioral control significantly shape the intention to adopt Islamic finance. Mediation analysis further reveals that attitude mediates the effects of religiosity, awareness, and financial literacy on adoption intention, whereas knowledge shows no significant influence. These findings highlight that internal factors only foster adoption intention when translated into positive attitudes toward Islamic financial products. Theoretically, this study extends TPB by incorporating religiosity, awareness, and financial literacy as essential predictors. Practically, it suggests that Islamic financial institutions should strengthen financial literacy programs, emphasize religious values, and enhance awareness campaigns to build favorable attitudes and increase adoption. Although limited to one region and a cross-sectional design, the study lays a foundation for future research using longitudinal approaches and exploring additional variables such as trust and perceived risk.